Legitimasi Pencabutan Kewarganegaraan dalam Hukum Hak Asasi Manusia Internasional: Studi Kasus di Nikaragua - Calvin Paulus Marcelito Simanjuntak; Diajeng Wulan Christianti (Badan Strategi Kebijakan Hukum, 2025)
The right to nationality is a fundamental prerequisite for accessing other human rights, yet its arbitrary deprivation remains a critical concern under international law. This study examines Nicaragua's Laws No. 1055 and 1145, which authorize the revocation of citizenship based on an expanded and ambiguous definition of